Assessment of Myocardial Mechanics in Acute Rheumatic Fever Using Speckle-Tracking Echocardiography - Utku Pamuk; Hazım Alper Gürsu; Emine Azak; İbrahim İlker Çetin (Anatolian Journal of Cardiology, 2023)
Background: This study aims to evaluate the role of speckle-tracking echocardiography to identify myocardial deformation in acute rheumatic fever.